234k views
1 vote
Find the product : (6x-1) (5x+2) =

User OusecTic
by
4.7k points

2 Answers

6 votes

Answer:

Explanation:

The solution is in the attached file

Find the product : (6x-1) (5x+2) =-example-1
Find the product : (6x-1) (5x+2) =-example-2
User Simon Alford
by
4.9k points
6 votes

Answer:


30x^2+7x-2

Explanation:

Use the foil method/distribute:

(6x-1)(5x+2):

Breaks apart into: (6x)(5x) = 30x^2

Multiply the next term:(6x)(2)=12x

Then the next: (-1)(5x)=-5x

Last term: (-1)(2)=-2

Combine them to get: 30x^2+12x-5x-2

Simplify: 30x^2+7x-2

User Moyano
by
5.7k points